Luctus est istic tuus,/ crimen novercae. Boskie i ludzkie szaleństwo Heraklesa na podstawie tragedii Eurypidesa i Seneki - Karamucka, Magdalena (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The article aims to examine the tragedies: Ήρακλής μαινόμενος by Euripides and Hercules Furens by Seneca and exactly the different types of the madness, by which the main character is overcome in the above mentioned dramas. Although the article touches also on the issue of the insanity sent to the hero by Hera/ Juno, concentrates especially on the fit of madness, that is here defined as a human madness.
Luctus est istic tuus,/ crimen novercae. Divine and human madness of Heracles according to the dramas by Euripides and Seneca
One of the main, initial thesis of the article is that in the tragedies `Hρακλής μαινόμενος by Euripides and Hercules Furens by Seneca the main character falls into the madness twice. The first madness is sent by Hera/ Juno and is here defined, because of its origin, as a divine madness. The second one is so called human madness and Heracles/ Hercules is most probably overcome by it, after he has recognised, that he, driven by the involuntary fury, killed his own wife and sons. This state of the psyche of the hero is already independent from the deity and originates in such deeply human feelings like despair, anger, pain, shame. The strongly stirred hero plans to commit a suicide. According to the contemporary psychology this situation can be, because of some reasons analysed in the article, recognised as a symptom of irrationality. In the drama by Seneca Amfithryon, the father of the hero also defines the state of Hercules, who has become aware of the truth about his deeds, outright as furor. There is in the drama by Euripides, however, no reference to this second madness, which is connected with the somewhat different mentality that the drama originated in (the still kept in memory Homeric ethos and the attitudes towards the issues of honour, suicide etc. determined by it). Seneca as a stoic noticed and emphasized – although he generally also accepted the suicide – that Hercules, because of the anger, acts irrationally and, as a result, is in fact mentally unable to decide about his life and death. In the article is also presented in what an interesting way the above mentioned differences in the mentality of Euripides and Seneca manifest themselves in the case of the divine madness (among other things, the difference between Greek Lyssa and Roman Furor).
Keywords: Heracles; anger; Euripides; Suicide; Seneca; Madness